Current state of the alcohol industry in Ukraine - Pivchuk, Yulia; Kovalchuk, Olga (My University, 2014)
Food industry is the main part of light industry of Ukraine. During the period of market economy reform in the food industry as well as in the alcohol industry, there are some changes that do not always have a positive effect. Therefore it is important to assess the current state of the alcohol industry and perspectives of its development.
Keywords: alcohol industry; development; market economy; ринкова економіка; розвиток; спиртова промисловість; рыночная экономика; развитие; спиртовая промышленность; кафедра ділової іноземної мови та міжнародної комунікації